2020
DOI: 10.3390/app10155316
|View full text |Cite
|
Sign up to set email alerts
|

Off-Design Operation of Conventional and Phase-Change CO2 Capture Solvents and Mixtures: A Systematic Assessment Approach

Abstract: Solvent-based CO2 capture technologies hold promise for future implementation but conventional solvents incur significant energy penalties and capture costs. Phase-change solvents enable a significant reduction in the regeneration energy but their performance has only been investigated under steady-state operation. In the current work, we employed a systematic approach for the evaluation of conventional solvents and mixtures, as well as phase-change solvents under the influence of disturbances. Sensitivity ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…DMCA, (Papadopoulos et al 2020b). The phase split solvent is proved to be advisable from economic (Zarogiannis et al 2020a), environmental (Shavalieva et al 2021) and operational (resilient to disturbances) (Zarogiannis et al 2020b) points of view. This study proposes a fast method that, based solely on experimental data of vapour-liquid equilibrium of CO 2 gas, compares alternatives with MEA in terms of required flowrate and energy consumption.…”
Section: Alternative Aqueous Alkanolamines To Meamentioning
confidence: 99%
“…DMCA, (Papadopoulos et al 2020b). The phase split solvent is proved to be advisable from economic (Zarogiannis et al 2020a), environmental (Shavalieva et al 2021) and operational (resilient to disturbances) (Zarogiannis et al 2020b) points of view. This study proposes a fast method that, based solely on experimental data of vapour-liquid equilibrium of CO 2 gas, compares alternatives with MEA in terms of required flowrate and energy consumption.…”
Section: Alternative Aqueous Alkanolamines To Meamentioning
confidence: 99%
“…Pore-scale simulations showed that CWI altered the wettability of the carbonate rock from neutral to water-wet. Zarogiannis et al [2] employed a systematic approach to identify the impact that operating parameter variations and different solvents exert on multiple CO 2 capture performance indicators. Moita et al [3] examined experimentally the mineral carbonation of CO 2 in plutonic ophiolitic mafic rocks through a set of laboratory experiments on cumulate gabbro and gabbro-diorite specimens from the Sines Massif (Portugal).…”
mentioning
confidence: 99%